Isolation and Characterization of Phenolic Glycoside from the Bark of Symplocos RacemosaRoxb. Issue Volume 7:Issue S1(2010) (2010) - Vijayabaskaran, M.; Yuvaraja, K. R.; Babu, G.; Perumal, P.; Jayakar, B.
Abstract : A new phenolic glycoside, 3, 5 - dihydroxy - 2- (hydroxyl methyl) - 6-(3, 4, 5-trimethoxy phenoxy)tetrahydro-2 H -pyran-4-yl, 4-hydroxy-3-methoxy benzoate have been isolated from the dried bark of Symplocos racemosa . The structure was identified by extensive spectral analysis, especially FT-IR, GC-MS, 1 H NMR and 13 C NMR techniques. The method of isolation was simple, cost effective and efficient. The preliminary bioactivity of the compound was also evaluated. The ethanolic extract of Symplocos racemosa (EESR) was investigated for its anti-pyretic activity against brewer's yeast induced pyrexia. The antipyretic effect of EESR (measured as % reduction in body temperature) was compared with paracetamol (100 mg/kg, orally). EESR in dose of 200 mg/kg caused significant decrease in body temperature of rats. This study has established the antipyretic activity of Symplocos racemosa and thus, justifies the ethnic uses of the plant.